Diagnostic Challenges of Intra-operative Frozen Consultation for Mammary Epithelioid Myofibroblastoma. (September 2022) - Zeng, Ying; Wang, Qianhui; Jiang, Xin; Yao, Hui; Wang, Xue; Tang, Xuefeng
Myofibroblastoma (MFB) of the breast is a rare benign neoplasm that exhibits several morphologic variants and presents diagnostic challenges for pathologists, especially in recognizing intra-operative frozen sections. In order to raise awareness of this tumor and avoid misdiagnosis, we describe a case of a 38-year-old female patient diagnosed as epithelioid MFB. This painless tumor was well-circumscribed, found in the left breast and was physically examined over a period of six months. Histologically, this tumor was predominantly composed of epithelioid cells, which arranged as single cells, small clusters or nests. Tumor stroma was collagenized with spindle cells, adipose and focal myxoid areas. This case was misinterpreted as invasive carcinoma in the frozen section. The immunohistochemical profile demonstrated positivity for Vimentin, desmin, SMA, calponin, CD34, ER, PR and AR, whereas pan-keratin, keratin 7, keratin 34βE12, keratin 5/6, EMA, p63 and S100 were negative. RB1 was abnormally negative, confirming the diagnosis of epithelioid MFB. Making a correct diagnosis is primarily dependent on awareness by the pathologist of this unusual variant of MFB and careful integration of clinicopathologic findings to avoid potential diagnostic pitfalls.